Integrasi Seven Quality Control Tools dan FMEA dalam Analisis Pengendalian Kualitas Kendaraan Bertenaga Listrik: Sebuah Tinjauan Literatur - Raehan Wisnu Wardana; Bambang Handoko; Widya Retno Prasinta; Anwar Samsa (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The transition from conventional vehicles to electric vehicles offers a sustainable urban transportation solution. However, the reliability of electric vehicles, as the primary propulsion component, is critical to safety and operational efficiency. This literature review aims to analyze the application of quality control methods, specifically the Seven Quality Control Tools and Failure Mode and Effect Analysis (FMEA), in maintaining electric vehicle performance in electric vehicles. The review method was conducted by synthesizing previous research related to electric vehicle failures, quality control tools, and risk management in the automotive and manufacturing industries. The review results indicate that the Seven Quality Control Tools are effective in identifying historical defect patterns such as overheating and bearing failure, while FMEA provides a proactive approach for calculating the Risk Priority Number (RPN) to prioritize mitigation actions. The integration of these two methods offers a comprehensive framework for improving product quality and operational reliability. It is concluded that the combination of reactive analysis (Seven Quality Control Tools) with proactive risk assessment (FMEA) is crucial for the development of reliable electric vehicle systems.